1998
DOI: 10.1136/sti.74.2.120
|View full text |Cite
|
Sign up to set email alerts
|

Community based study of sexually transmitted diseases in rural women in the highlands of Papua New Guinea: prevalence and risk factors

Abstract: Objective: To estimate the prevalence of sexually transmitted diseases (STDs) and determine their risk factors/markers among a rural population of women in the highlands of Papua New Guinea. Methods: Community based random cluster sample of women of reproductive age were interviewed and examined and had specimens collected for laboratory confirmation of chlamydial and trichomonal infection, gonorrhoea, syphilis, and bacterial vaginosis. Results: Chlamydia trachomatis was detected in 26%, Trichomonas vaginalis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
35
0
1

Year Published

2000
2000
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 13 publications
(15 reference statements)
7
35
0
1
Order By: Relevance
“…15, 18,, 20, 14, 19 The infection rate is quite similar to another study in Nepal, New Guinea. 12,16 The higher rate in the other studies may be attributed to a wider age range of participants and the fact that adolescent women had been sexually active. It is difficult to compare the incidence of STIs in one region with that of other because of different medical, social and economical factors.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…15, 18,, 20, 14, 19 The infection rate is quite similar to another study in Nepal, New Guinea. 12,16 The higher rate in the other studies may be attributed to a wider age range of participants and the fact that adolescent women had been sexually active. It is difficult to compare the incidence of STIs in one region with that of other because of different medical, social and economical factors.…”
Section: Discussionmentioning
confidence: 70%
“…19 In this study gonococcal infection rate was much higher than elsewhere. 15,16,17,18,19,20 The organism Neisseria gonorrhoeae is associated with behavior of persons. Nepal is still largely a traditional country and multiple sex partners of married women are very rare due to cultural, legal and social taboos.…”
Section: Discussionmentioning
confidence: 99%
“…Results were analyzed using a one-tailed Fisher's exact test in a pair-wise comparison of the three treatments with placebo. 5 Mice received a 3 ϫ 10 6 T. vaginalis intravaginal challenge 5 min after intravaginal pre-treatment. Number of infected mice divided by the number of mice per group.…”
Section: Methodsmentioning
confidence: 99%
“…1,9,10 In this study, the finding of G. vaginalis as the most commonly isolated organism, with a prevalence rate of 28%, is in agreement with other studies that showed different rates ranging from 9% to 53%. 4,9,[11][12][13][14][15] These variations in the rates could be related to geographical distribution or systematic differences in the various population samples, however, there is continuing controversy about its importance as a pathogen and its ability to cause vaginitis. 4,16 The term "bacterial vaginosis" (BV) is a variant of bacterial vaginitis and is the most prevalent vaginal infection.…”
Section: Discussionmentioning
confidence: 99%